Strategi Media Relasi PT. United Tractor Tbk Dalam Menjalin Hubungan Dengan Media - Michelle Imanuela Maria Sirap; George Nicholas Huwae (Jurnal Ilmiah Wahana Pendidikan, 2023)
Media relations are an important activity that directly relates to external parties and is carried out by the Corporate Communication team of PT. United Tractors Tbk to disseminate information, obtain publicity through mass media, and maintain the company's image. Recognizing the important role of the mass media in the sustainability of a company, there is no other way for an institution but to open itself to the media and optimize its function and role as a public relations practitioner in building good relationships with the media. Therefore, the purpose of this research is to identify the media relations strategies applied by PT. United Tractors Tbk in building relationships with the media.This research was conducted using a qualitative descriptive method, with data presented in the form of descriptive data through written words. Research findings were obtained from interviews. Data analysis was carried out using data reduction techniques. The model used in this study is the two-way symmetric model. The results of this study show that the relationship between PT. United Tractors and the media is effectively managed through the help of a third-party agency through well-planned media relations activities, thus creating a good and mutually beneficial approach for both parties.